Corporate Culture of Future Officers of the Armed Forces of Ukraine as a Scientific and Pedagogical Problem - Volodymyr Seliuk (Pedagogical Discourse, 2022)
The article analyzes various perspectives on the issue of corporate culture formation. It has been determined that the views of Ukrainian scholars are grounded in the research conducted by foreign scholars, who laid the foundations for comprehending the concept of "corporate culture" as a vital component of human resources management and general administration. Furthermore, the study reveals that there are more than 20 different definitions of the concept under examination. While some researchers regard organizational and corporate culture as synonymous, a majority discern significant differences between these terms.Corporate culture takes shape within diverse organizations and institutions, prompting its examination as a crucial component across various disciplines, including management, economics, sociology, psychology, pedagogy, etc. Simultaneously, the essential features of the concept are scrutinized with a focus on the relevant industry. In the context of modern military conditions, it is imperative to investigate the state and process of corporate culture formation within military and paramilitary formations and units.It is established that the study of the corporate culture of officers is conducted in the bodies of internal affairs, the National Guard, the Armed Forces of Ukraine, and the State Border Guard Service of Ukraine. Simultaneously, researchers describe quite similar issues and identify similar negative factors that impede the qualitative formation of corporate culture. In addition to describing the state of the problem, the research results in proposals for overcoming the impact of negative factors. It was found that the ways of improvement proposed by the authors also share common features. This makes it possible to scale the results of scientific research to all military formations in Ukraine.